Pediatric split liver transplantation in a patient with biliary atresia polysplenia syndrome and agenesis of inferior vena cava - Jung-Man Namgoong; Shin Hwang; Dae-Yeon Kim; Tae-Yong Ha; Gi-Won Song; Dong-Hwan Jung; Kyung Mo Kim; Seak Hee Oh (Korean Journal of Transplantation, 2020)
Biliary atresia (BA)-polysplenia syndrome (PS) is diagnosed in a small proportion of BA patients. We present a case of split liver transplantation (LT) successfully performed in a pediatric recipient with BA-PS. The recipient was 29-month-old boy who underwent Kasai procedure. The coexisting malformations included agenesis of the inferior vena cava with azygos vein continuation, polysplenia, intestinal malrotation, truncated pancreas, and preduodenal portal vein and annular pancreas. With pediatric end-stage liver disease score of 33, the patient was allocated for split LT. Under this condition, the left lateral section graft was equivalent to a graft-recipient weight ratio of 2.6%. The recipient surgery was performed according to the standard procedures of pediatric LT. The graft hepatic vein was directly anastomosed with the suprahepatic confluence of the recipient hepatic veins. An external iliac vein homograft was interposed for portal vein reconstruction. Portal collateral veins were embolized intraoperatively to secure portal vein inflow. No surgical complications were developed. Currently, the patient has been doing well for 4 years after transplantation. Our pediatric patient with BA-PS had various anatomical malformations. Thorough preoperative and intraoperative assessment of these anomalies, adoption of customized reconstruction techniques of LT, and careful posttransplant monitoring are necessary for successful LT.